2017
DOI: 10.21699/jns.v6i2.528
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simultaneous Nasogastric and Nasojejunal Tubes for Proximal Intestinal Atresias - A Preliminary Report

Abstract: Please see fulltext.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Moreover, our study revealed that the JFT group achieved earlier enteral feeding than non-JFT feeding. It has been shown that early enteral feeding is very important for patients with CDO after surgery for wound healing and general well-being [ 12 , 13 ]. Furthermore, enteral feeding also has improved the bowel peristalsis after anastomosis and reduced the complications due to parenteral nutrition [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our study revealed that the JFT group achieved earlier enteral feeding than non-JFT feeding. It has been shown that early enteral feeding is very important for patients with CDO after surgery for wound healing and general well-being [ 12 , 13 ]. Furthermore, enteral feeding also has improved the bowel peristalsis after anastomosis and reduced the complications due to parenteral nutrition [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…They all have some advantages and disadvantages [ 10 16 ]. For uses of jejunal feeding tubes, these are usually divided into two methods: through a TAT [ 10 , 13 ] or a post-anastomosis per-cutaneous transperitoneal JFT [ 11 ]. To the best of our knowledge, all previous studies [ 10 , 12 16 ], except one [ 11 ], applied the TAT and not JFT for their CDO infants during Kimura surgery.…”
Section: Discussionmentioning
confidence: 99%